Coulomb frustration of the multiphoton ionization of metallic clusters under intense EUV FEL evidenced by ion spectrometry. (6th October 2015) - Mazza, T; Devetta, M; Milani, P; Motomura, K; Liu, X-J; Fukuzawa, H; Yamada, A; Okunishi, M; Nagaya, K; Iwayama, H; Sugishima, A; Mizoguchi, Y; et al.
Abstract: Free electron laser light sources delivering high intensity pulses of short wavelength radiation are opening novel possibilities for the investigation of matter at the nanoscale and for the discovery and understanding of new physical processes occurring at the exotic transient states they make accessible. Strong ionization of atomic constituents of a nano-sized sample is a representative example of such processes and the understanding of ionization dynamics is crucial for a realistic description of the experiments. We report here on multiple ionization experiments on free clusters of titanium, a high cohesive energy metal. The time of flight ion spectra reveal a saturation of the cluster ionization at ∼10 16 photons per pulse per cm 2 . Our results also show a clear lack of any explosion process, opposite to what is observed for a rare-gas cluster under similar conditions. A simple and generalized multi-step ionization model including Coulomb frustration of the photoemission process effectively reproduces with a good agreement the main features of the experimental observation and points to an interpretation of the data involving a substantial energy deposition into the cluster through electronic system heating upon scattering events within photoemission.